Effect of Dietary supplementation of essential oil on immune response, blood biochemicals, carcass quality traits and Gut microbiota analysis of japanese quail birds (Coturnix coturnix japonica) - TIWARI, Dr. ABHISHEK (The Indian Journal of Animal Sciences, 2026)
The present study was conducted to evaluate the effects of dietary supplementation of essential oils on gut immune response, blood biochemical parameters, microflora,  and carcass quality traits in Japanese quail. A total of 200 day-old quail chicks were randomly allotted to five dietary treatments with four replicates of 10 birds each and reared for 35 days. The treatments consisted of a basal diet (control), a basal diet supplemented with cinnamon oil (500 ppm), peppermint oil (500 ppm), a combination of cinnamon and peppermint oils (250 ppm each), and a combination of cinnamon and peppermint oils (500 ppm each). At the end of the feeding trial, blood samples were collected to determine biochemical parameters, metabolites, and enzyme activities. Gut microbiota analysis was performed by enumerating Escherichia coli from cecal contents using selective culture media. Dietary supplementation of essential oils reduced cecal E. coli population and improved immune response as indicated by increased IgG concentration and lymphocyte percentage in supplemented groups. Serum cholesterol and creatinine levels were lower in birds receiving essential oils, while liver enzyme activities remained within the normal physiological range. Carcass evaluation showed improvement in dressing percentage in birds supplemented with cinnamon oil and peppermint oil. The results indicate that dietary supplementation of cinnamon and peppermint essential oils, individually or in combination, enhances immune response, improves carcass characteristics, and modulates gut microbial population without adverse effects on blood biochemical parameters in Japanese quails.